Enhanced Antithrombotic Mechanisms in Patients with Maturity-Onset Diabetes mellitus without Thromboembolic Complications - Grignani, G; Gamba, G; Geroldi, D; Pacchiarini, L; Solerte, B; Ferrari, E; Ascario, E (Thrombosis and Haemostasis, 1981)
Some haemostatic parameters have been evaluated in a group of rigorously selected patients with maturity-onset diabetes mellitus without thromboembolic complications and in apparently normal subjects of the same age before and after the venous occlusion test (VOT).In basal conditions diabetics had higher levels of AT III as biological activity and higher fibrinolytic and antifibrinolytic activities than controlsAfter VOT, F VIII R:Ag increased significantly in both groups, more markedly in controls than in diabetics, while F VIII: C showed no modification.Also AT III R:Ag increased after the test, but such variation was significant only in diabetics; on the contrary, the biological activity of AT III was always significantly decreased after the test.After VOT there were also in both groups highly significant increases in the fibrinolytic and antifibrinolytic activities.Finally, HbA1c levels directly correlated with AT III as biological activity before VOT, but with no other parameter either before or after the test.These data suggest the existence in patients with diabetes mellitus without thromboembolic complications of an activated protective mechanism against intravascular clotting.
Keywords: Antithrombotic mechanisms; Diabetes without thromboembolic complications; Antithrombin III; Plasminogen activator